Pemanfaatan Vegetasi Sekunder Dan Limbah Serbukgergaji Sebagai Pupuk Bokasi Pluspada Budidaya Tanaman Hortikultura Dalam Sistem Intercropping - Aysyah Anas, Arsy; Mila Rahni, Nini; Nur Isnian, Sitti (Amaliah: Jurnal Pengabdian Masyarakat, 2025)
he horticultural plants was foodstuffs that was needed by the body because they contain several vitamins, minerals, proteins and carbohydrates. This commodity has a fairly high economic value and the level of deman tends to increase from year to year, but is not supported by an increase in production. This was due to the fact that most of the horticultural cultivation was done on marginal land and inadequate cultivation techniques. In Muna District, especially Sub-District Watopute has a wide potential for the development of this comodity, like vegetables. However, these lands was dominated by marginal dry land. The biotechnology of organic based fertilizer is a technological innovation that can increase the availability of horticultural products. The comunity partnership program (PKM) is a very appropriate program to disseminate innovative biotechnology so that it can be adopted by the wider community. In addition, the intercropping system can improve the efficiency crop yield per unit of land area while maintaining soil fertility and increasing crop resistance.